Antibiotic-loaded Porous Alumina Ceramic for One-stage Surgery for Chronic Osteomyelitis. (November 2018) - Fiorenza, Fabrice; Durox, Hélène; El Balkhi, Souleiman; Denes, Eric
Abstract : The classic treatment of chronic osteomyelitis is usually a two-stage surgery combined with systemic antibiotic therapy for several months. We report the case of a patient presenting a chronic osteomyelitis caused by methicillin-resistant Staphylococcus aureus who was treated with a one-stage surgery using an antibiotic-loaded ceramic. We used a porous alumina ceramic loaded with gentamicin to reconstruct the bone removed during débridement and to avoid its colonization. All bacteriological samples performed before and during the surgery revealed the presence of a methicillin-resistant S aureus . Because of the local release of the antibiotic, very high concentrations (more than 50 times the concentration needed) were administered in the surgical wound, thus helping to cure the infection. Owing to the strength of the ceramic, the patient was allowed to walk 10 days after the surgery. After a follow-up at 14 months, the patient is well-being, without any relapse of the infection. The CT-scan follow-up shows an osseointegration of the ceramic. Even, if it is too early to tell that infection is completely cured, these first results are encouraging for the use, in the future, of this antibiotic-loaded ceramic for complex bone infection.